'JENGAH' (Self- Consciousness) and Its Value Transformation: A Road Toward Good Governance at Bali Province - WINGARTA, I PUTU; ABDULLAH, IRWAN; SURYO, DJOKO (Universitas Muhammadiyah Yogyakarta, 2012)
Globalization and its threat continuously endanger Bali, an Island with natural and culturaluniqueness, as well as one of the 33 provinces in Indonesia. This study aims to find out, how big athreat that endangers the contemporary Bali, and the role of ‘jengah’ (self-consciousness) to face theglobalization. It is found in the research that ‘jengah’ and its value transformation in it gives positivecontribution to face the threat and those values can guarantee the sustainability of Bali uniqueness inthe future. The research was conducted at Bali Province Government or ‘Pemprov Bali’. The researchshowed that by transforming the ‘jengah’ (self-consciousness) values, Bali Province Governmentsucceeded in improving its good governance as well as the apparatuses sense of nationalism. Thevalues also gave the positive impact to prevent the swift threat on Bali uniqueness.